Caracterização do sistema de co-cultivo de microalgas e cianobactérias dulcícolas com objetivo de avaliar seu potencial para obtenção de biomassa, óleo, biodiesel in situ e biochar - Guerra, Witter Duarte (2024)
Microalgae and cyanobacteria are gaining prominence in the field of biofuels due to their high potential for lipid and biomass accumulation. This characteristic makes them promising raw materials for the production of biodiesel, in situ biodiesel, and biochar. Microalgae co-culture is one of the main strategies to promote positive outcomes related to biofuel synthesis. In algae-cyanobacteria systems, algae grow in groups or colonies that interact or compete with each other. Cooperative interactions among microalgae can enhance nutrient utilization within the system and promote the growth of both microalgae and cyanobacteria. Biological, physical, and chemical factors directly affect the metabolic storage of nutrient reserves in microalgae and cyanobacteria, which can interfere with co-cultivation. To develop optimized methods for lipid production from co-culture, it is important to explore methodologies that improve biomass growth and harvesting systems. This study aimed to optimize the cultivation of the microalga Chlorella sp. and the cyanobacterium Oscillatoria sp. in a co-culture system for the subsequent production of lipids, biomass, in situ biodiesel, and biochar. The co-culture was conducted in glass reactors in batch mode, with aeration maintained throughout the cultivation period at an ambient temperature of 25 °C ± 1 °C. The cultivation lasted 21 days, with a controlled photoperiod of 12 hours of light and 12 hours of dark. The nutritional conditions tested included phosphate, nitrate, and zinc levels, according to the Dohlert experimental design, to ensure the yield of biomass, lipids, biodiesel, and biochar. The results indicated that the experimental methodology for co-cultivation led to a 43.45% increase in lipid content with the following final concentrations: phosphate 22.400 g, nitrate 0.255 g, and zinc 0.030 g. In terms of biomass, there was a 64.53% increase with the final values of phosphate 22.400 g, nitrate 0.170 g, and zinc 0.480 g. The interactions between the different species of microalgae and cyanobacteria were positive, resulting in yields higher than those reported in the literature for other species of microalgae and cyanobacteria.